2016
DOI: 10.1177/1526602816668306
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Fractional Flow Reserve to Predict Restenosis After Superficial Femoral Artery Stenting

Abstract: Poststenting mean FFR is useful for predicting restenosis in SFA disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…If a significant adjusted mortality difference was found between races, a prespecified mediation analysis was planned to investigate the potential role of variations in procedural and postprocedural care in driving this difference. Procedural and postprocedural factors considered in the analyses included the following: (1) the use of advanced intracoronary imaging or physiologic testing (fractional flow reserve [FFR], 22 intravascular ultrasound [IVUS], 23 or optical coherence tomography [OCT]); (2) bare-metal stent (BMS) vs drug-eluting stent (DES) use; (3) incomplete revascularization; (4) radial access use; and (5) postprocedural medication prescriptions (high-intensity statins, β-blockers, angiotensin-converting enzyme inhibitor [ACEi] or aldosterone receptor blocker [ARB] therapy, and clopidogrel bisulfate, ticagrelor, or prasugrel). Performance of FFR, IVUS, or OCT included the use of this technology during the diagnostic catheterization, PCI, or both.…”
Section: Procedural and Postprocedural Carementioning
confidence: 99%
“…If a significant adjusted mortality difference was found between races, a prespecified mediation analysis was planned to investigate the potential role of variations in procedural and postprocedural care in driving this difference. Procedural and postprocedural factors considered in the analyses included the following: (1) the use of advanced intracoronary imaging or physiologic testing (fractional flow reserve [FFR], 22 intravascular ultrasound [IVUS], 23 or optical coherence tomography [OCT]); (2) bare-metal stent (BMS) vs drug-eluting stent (DES) use; (3) incomplete revascularization; (4) radial access use; and (5) postprocedural medication prescriptions (high-intensity statins, β-blockers, angiotensin-converting enzyme inhibitor [ACEi] or aldosterone receptor blocker [ARB] therapy, and clopidogrel bisulfate, ticagrelor, or prasugrel). Performance of FFR, IVUS, or OCT included the use of this technology during the diagnostic catheterization, PCI, or both.…”
Section: Procedural and Postprocedural Carementioning
confidence: 99%
“…8,13) In terms of pressure study, FFR ≤0.92 after EVT predicted in-stent restenosis in the SFA. 7) VFR, measured by a thermodilution method after EVT, predicted limb prognosis in critical limb ischemia patients. 14) It is not clear whether pressure- and velocity-based parameters predict limb prognosis, such as lesion restenosis or amputation free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported translesional pressure measurement, with pressure sensor wires, to calculate FFR in peripheral arterial diseases. 57) In pathophysiological conditions, such as stenosis of the superficial femoral artery (SFA), stenosis resistance may increase, but the relationship between stenosis resistance and stenotic severity remains to be seen. We aimed to elucidate SFA stenosis resistance’s pathophysiological significance at maximal hyperemia.…”
Section: Introductionmentioning
confidence: 99%
“…A post-intervention PFFR of <0.95 was associated with a significant increase in PSV. Later on, Kobayashi et al conducted a single center nonrandomized prospective study to demonstrate the relation of post-intervention PFFR and future risk of restenosis [22]. The authors administered papaverine 30 mg to induce hyperemia and PFFR was measured using 0.014-inch Pressure Wire Aeris G8 (St. Jude Medical).…”
Section: Reviewmentioning
confidence: 99%